Christian names and surnames in the common vocabulary of Peru: Carolina, Natacha, Zambrano, Rambo, Huaman... - Lovón Cueva, Marco Antonio (2012)
In Peruvian popular speech personal names are often used for referring to inanimate things (“Cervantes” for “cerveza” [beer], to activities (“Baylón” for “dance”, “ball”), to qualifying adjectives (“Carolina” for “caro” dear [of price]), affirmatives (“Silverio” for “yes”, [“sí”]) and negations (“Nelson” for “no”). This is a very common expedient which consists in replacing names, adjectives and adverbs by proper names and approximate homophones and comes mainly from slang, and reaches all common forms of popular speech. To all these creations must be added the proper names used for material beings who suggest a special connection of semantic relationship (Natacha is then used for “household maid”, and Rambo for “policeman”). This mechanism in which common names are made to replace the names of common words is called ‘eponymy’ a phenomenon that our lexicology has taken little notice of and is not much used in Peruvian lexicography. For this reason, in the following study we hope to reveal the modal behaviour that takes place in the creation of Peruvian eponyms; the phonetic analogy that functions principally on Christian names and surnames of people, such as, for example, Zambrano to say “zambo” “knockkneed”(patituerto) and also “coloured”; and also the semantic analogy which tends to reflect the names of people in television, serial plays and the cultural atmosphere in general. As well as this, in this study, we are giving lexicographical treatment to each of the words so used in the form of special references and mottos. The information in thisinvestigation has been picked up in verbal sources, written sources and internet, the same as those used in the Dictionary of Americanisms. With this piece of work it is also hoped to add something to one of the more peripheral fields of lexicology and general lexicography.